Optimum planting date for the maximum tuber yield of tropical sugar beet (Beta vulgaris L.) genotypes in the Old Brahmaputra Floodplain - Hossain, M. M.; Kader, M. A.; Kashem, M. A. (Journal of Scientific Agriculture, 2021)
Planting dates for a crop is a non-monetary input but plays a significant role in increasing the yield crop. Therefore, identifying genotype-specific planting dates is essential for obtaining the economic yield of tropical sugar beet. From this perspective, a field experiment was conducted at the Agronomy Field Laboratory, Bangladesh Agricultural University in Bangladesh, from November 2015 to April 2016. Five sugar beet genotypes: Shubhra, Cauvery, EB-0616, EB-0626, and EB-0809 planted on four dates: 10, 20, 30 November, and 10 December. Treatments were laid out in a split-plot design replicated three times. Data revealed that planting on 10 November date, genotype EB-0809 produced the highest tuber yield, which was significantly superior to any other genotype combined with other planting dates. It was found that every ten days delay of planting from 10 November to 30 December reduced the tuber yield by 30, 43, and 55%, respectively. Results confirmed that planting the EB-0809 genotype on 10 November is ideal to obtain the highest tuber yield of tropical sugar beet in Bangladesh.